Response of Rice Tissue and Callus to Culture Filtrate of Magnaporthe grisea (Pyricularia oryzae Cav.) In Vitro - Singburaudom, Narong; Chuntharathin, Petcharat; Rukvidhayasartra, Vijai; Sripichitt, Prapa (Agriculture and Natural Resources, 1998)
The responses of rice tissue to culture filtrate of the fungus Magnaporthe grisea (Pyricularia oryzae Cav.), the causal agent of rice blast were investigated in vitro. Shoots and calluses of rice variety KDML105 were cultured on medium containing culture filtrate at concentrations of 0:9,1:9, 2:9, 3:9, 4:9 and 5:9 by volume, respectively. The result indicated that rice shoots exhibited significant difference response to different culture filtrate concentrations. Where the concentrations of culture filtrate increased, the height, number and survival of shoots decreased. At the concentration of 2:9, the height and number of shoots were reduced to 50 percent. The increasing of culturing period had an influence on the increasing of height and the number of shoots while the survival of shoots were reduced. Some of brown tissue could reproduce newly emerged shoots after culturing for a longer period. The responses of calluses to culture filtrate were investigated. The results revealed that where the concentrations of culture filtrate were increased, the calluses color became brown, while the diameter of calluses, amount of green spot formations and the number of regenerated shoots were reduced. At the concentration of 2:9, callus diameter was reduced to 50 percent, the callus color was changed to brown 50 percent, the percentage of green spot formations and the regenerated shoots were the highest at 3.6 and 12.5 percent, respectively. The result suggested that culturing period had a significant influence on callus development. On induction medium, while the culturing period was increased, the size of calli, degree of yellowing and green spot formations were increased whereas the color of calli was changed to brown, the number of survival was reduced and the number of regenerated shoots were increased when they were cultured on a regeneration medium.